Peningkatan kapasitas lansia dalam mencegah cedera melalui latihan keseimbangan postural dengan media Balance Ball - Hidayatullah, Muhammad Riyan; Evitamala, Lilik; Suprawesta, Lalu (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
Elderly individuals often face the risk of falls and injuries, which can significantly impact their overall quality of life. To address this issue, targeted interventions are needed to enhance their balance and physical fitness. This community service program aimed to provide training on physical activity models using Balance Ball media to improve organ function, muscle strength, balance, and prevent the risk of falls or injuries. The program was conducted at the Tresna Werdha Mandalika Social Institution in Mataram, involving 30 elderly participants. The implementation methods included socialization, training, technology application, mentoring, and program sustainability. The results demonstrated a significant improvement in participants' balance after completing the program. Before the training, 50% of the elderly exhibited poor balance, but this figure dropped to 3% post-training. Meanwhile, the percentage of those with moderate balance increased from 34% to 40%, and those with good balance rose from 16% to 57%. These improvements were supported by the participants' high enthusiasm and engagement throughout all stages of the program. This initiative is expected to provide tangible benefits for the elderly, enhance their well-being, and serve as a sustainable model for improving quality of life.